Glioblastoma Multiforme Cancer Stem Cells Express Components of the Renin–Angiotensin System - Bradshaw, Amy Ruth; Wickremesekera, Agadha Crisantha; Brasch, Helen D.; Chibnall, Alice M.; Davis, Paul F.; Tan, Swee T.; Itinteang, Tinte (Frontiers in Surgery, 2016)
Aim To investigate the expression of the renin-angiotensin system (RAS) in cancer stem cells (CSCs) we have previously characterized in glioblastoma multiforme (GBM). Methods 3,3-Diaminobenzidine (DAB) immunohistochemical (IHC) staining for the stem cell marker, SOX2 and components of the RAS: angiotensin converting enzyme (ACE), (pro)renin receptor (PRR), angiotensin II receptor 1 (ATIIR1) and receptor 2 (ATIIR2) on 4μm-thick formalin-fixed paraffin-embedded sections of previously characterized GBM samples in six patients was undertaken. Immunofluorescent (IF) IHC staining was performed to demonstrate expression of GFAP, SOX2, PRR, ACE, ATIIR1 and ATIIR2. The protein expression and the transcriptional activities of the genes encoding for ACE, PRR, ATIIR1 and ATIIR2 were studied using Western blotting (WB) and NanoString gene expression analysis, respectively. Results DAB and IF IHC staining demonstrated the expression SOX2 on the GFAP+ GBM CSCs. Cytoplasmic expression of PRR by the GFAP+ CSCs and the endothelium of the microvessels was observed. ACE was expressed on the endothelium of the microvessels only, while nuclear and cytoplasmic expression of ATIIR1 and ATIIR2 was observed on the endothelium of the microvessels and the CSCs. ATIIR1 was expressed on the GFAP+ CSCs cells and ATIIR2 was expressed by the SOX2+ CSCs. The expression of ACE, PRR and ATIIR1, but not ATIIR2 was confirmed by WB. NanoString gene analysis demonstrated transcriptional activation of ACE, PRR and ATIIR1, but not ATIIR2. Conclusion This study demonstrated the expression of PRR, ATIIR1 and ATIIR2 by the SOX2 CSC population, and ACE on the endothelium of the microvessels, within GBM. ACE, PRR and ATIIR1 were expressed at the protein and mRNA levels, with ATIIR2 detectable only by IHC staining. This novel finding suggests the CSCs may be a novel therapeutic target for GBM by modulation of the RAS.